Effects of Exciton Polarity in Charge-Transfer Polymer/PCBM Bulk Heterojunction Films - Rolczynski, Brian S.; Szarko, Jodi M.; Son, Hae Jung; Yu, Luping; Chen, Lin X. (American Chemical Society, 2014)
Charge-transfer copolymers with local electron density gradients, systematically modified by quantity and position of fluorination, result in widely variable (2-8%) power conversion efficiencies (PCEs). Ultrafast, near-infrared, transient absorption spectroscopy on the corresponding films reveals the influence of exciton polarity on ultrafast populations and decay dynamics for the charge-separated and charge-transfer states as well as their strong correlation to device PCEs. By using an excitation energy-dependent, dynamic red shift in the transient absorption signal for the polymer cation, the exciton polarity induced by push pull interactions within each polymer fragment is shown to enhance charge dissociation on time scales of tens to hundreds of picoseconds after excitation. These results suggest the important role played by the local electronic structure not only for exciton dissociation but also for device performance.